STRATEGI PEMBELAJARAN DALAM PENANAMAN NILAI-NILAI AGAMA ISLAM PADA ANAK BERKEBUTUHAN KHUSUS LARAS - Weriana Weriana; Fajri Ismail; M. Win Afgani (CV. ADIBA ASIHA AMIRA, 2023)
Every Indonesian child has the right to education, including children with special needs which are stated in RI Law no. 20 of 2003. Equal learning and educational opportunities for all children is a need that is considered very important for all human beings without any views that discriminate against children with special needs and normal children in general. However, the handling of children with special needs and normal children is clearly different. So it is necessary to study learning strategies for children with special needs in terms of instilling religious values. The method used is library research. Important principles in the learning of children with special needs are the principle of compassion, the principle of individual service, the principle of readiness, the principle of modeling. The learning models are psychodynamic models, biogenetic models, and behavioral models.